Becoming cruel: Appetitive aggression released by detrimental socialisation in former Congolese soldiers. (November 2013) - Weierstall, Roland; Haer, Roos; Banholzer, Lilli; Elbert, Thomas
Appetitive aggression – a rewarding perception of the perpetration of violence – seems to be an adaptation common to adverse conditions. Children raised within armed groups may develop attitudes and values that favour harming others when socialized within a combat force. Combatants who joined an armed force early in their lives should, therefore, perceive aggression in a more appetitive way than those who were recruited later. We interviewed 95 former members of armed groups operating in the eastern part of the Democratic Republic of the Congo. Those combatants that were having higher levels of appetitive aggression were those who joined a rebel force earlier in life. Surprisingly, neither the amount of military training nor the amount of time spent in the forces had a significant effect on the level of appetitive aggression. Our results show that when civil socialization is replaced by socialization within an armed group early in life, self-regulation of appetitive aggression may become deficient, leading to a higher propensity towards cruelty.